Combining early lower eyelid surgery with neuromuscular retraining for synkinesis prevention after facial palsy: the role of the eye in aberrant facial nerve regeneration - Di Stadio, Arianna; Ralli, Massimo; De Luca, Pietro; Sossamon, Jake; Frohman, Teresa C.; Altieri, Marta; La Mantia, Ignazio; Ferlito, Salvatore; Frohman, Elliot M.; Brenner, Michael J. (Frontiers in Neurology, 2024)
Background: Facial synkinesis (FS) is a distressing sequela of facial palsy (FP) characterized by involuntary, simultaneous movements of facial muscles occurring during voluntary facial expressions.Treatment of synkinesis is challenging, and preventive methods are needed.Aim: This study evaluated the efficacy of physical facial nerve rehabilitation (PFNR) therapy alone versus PNFR with eyelid surgery to correct lagophthalmos and prevent the onset of synkinesis.Methods: 25 outpatients were randomized to receive either PFNR alone (neuromuscular retraining and Kabat proprioceptive neuromuscular facilitation) or PNFR and early (90 days after FP onset) eyelid surgery (involving a conservative oculoplastic correction for lagophthalmos with epiphora or ectropion). Comprehensive otolaryngological assessments and Magnetic Resonance Imaging (MRI) were conducted. Synkinesis progression was measured using Another Disease Scale (ADS) at baseline, 3-, 6-, 12-, and 24-months post-treatment. The data were analyzed with ANOVA, t-test, Chi-Square analyses.Results: Patients undergoing eyelid surgery with PFNR showed faster (p<0.001) and better recovery of facial movements (p<0.05) than patients receiving PFNR alone comparing T0 and T12 (p<0.0001). No synkinesis were observed in the PFNR plus surgery group while 37% of patients in PFNR alone had synkinesis (p=0.03). At 24 months none of the patients in the surgery group presented synkinesis.Combining early surgical treatment of paralytic lagophthalmos or epiphora with PFNR accelerated functional recovery and reduced synkinesis in patients with FP compared to facial rehabilitation alone. Further investigations in larger populations with long-term follow-up are needed.